Determining factors for the creation of innovation-based ventures - Adalberto Escorcia; José Luis Ramos Ruiz; Rohemi Zuluaga-Ortiz; Enrique Delahoz-Domínguez (Journal of Innovation and Entrepreneurship, 2022)
This research aims to determine the impact of internal and external factors of Social Capital, Entrepreneurial Self-Efficacy, and Person-Entrepreneurship Fit in the transition of nascent entrepreneurs toward venture creation. For the development of this research, a sample of 500 entrepreneurs located in Colombia who are creating a company was taken. The research methodology is hypothetical-deductive with a cross-sectional multiple causal correlation design with an explanatory scope and is divided into three stages: first, an exploratory analysis of the data relating to the study variables is carried out. Second, a principal component analysis is carried out. Finally, the third stage is the modelling using the Partial Least Squares-Path Modelling methodology. Among the most relevant findings, it is found that Social Capital is significant in explaining Person-Entrepreneurship Fit. In turn, Social Capital and Person-Entrepreneurship Fit are significant in explaining Entrepreneurial Self-Efficacy. Finally, the construct of Venture Creation is only significantly explained by Person-Entrepreneurship Fit. Consequently, it can be concluded that the influence of social and psychological variables within the business cycle is significant, and models and strategies must consider these elements to design tools that support the optimal development of start-ups within the business cycle, so that they consolidate as stable ventures. This study contributes to filling the research gap by focusing on the factors determining the entrepreneurial process beyond its initial phase.
Keywords: 650; Entrepreneurial efficacy; Entrepreneurship; Partial Least Squares; Start-up; Venture creation